Análise numérica multiescala de meios porosos elasto-plásticos usando o método FE² direto - Moos, Eduardo Turra (2024)
Porous materials, especially those produced through additive manufacturing, have gained prominence due to their ability to offer lightweight, customized structures with optimized properties. However, microstructural heterogeneities, such as voids and inclusions, pose a significant challenge in accurately predicting their mechanical behavior, particularly in applications involving cyclic loading or requiring high structural reliability. In this context, multiscale numerical methods, such as the direct FE² method, stand out by enabling detailed analysis of interactions between micro and macro scales, maintaining a balance between precision and computational efficiency. In this study, the direct FE² method was used to analyze elastoplastic porous materials with cylindrical voids, considering void volume fractions ranging from 1% to 10%. Three distinct loading cases were investigated: simple tension, simple shear, and cantilever beam bending. Comparison with direct numerical simulations (DNS), where heterogeneities are fully modeled at a single scale, revealed that the direct FE² method exhibits high accuracy, with discrepancies below 2% for force-displacement curves and equivalent stress fields. Furthermore, the direct FE² method demonstrated a significant reduction in computational cost, requiring only about 50% of the processing time needed for DNS. The substantial computational advantage of the direct FE² method, which uses a fraction of the computational time required for DNS, makes it an attractive option for multiscale simulations of elastoplastic porous materials, offering precision, efficiency, and robustness.